PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS PELAKSANAAN KURIKULUM DI UPT SMP NEGERI 27 MEDAN - Ovi Ardilla; Abdul Fattah Nasution; Lilis Juliyanty Marbun; Lathifathun Nisa Hutabarat (Cendekia Madani Nusantara, 2026)
Principal leadership is a strategic factor that plays an important role in determining the success of the implementation of the Merdeka Curriculum in educational institutions. This study aims to analyze the influence of principal leadership on the effectiveness of the implementation of the Merdeka Curriculum at UPT SMP Negeri 27 Medan. This research employs a quantitative approach with an associative research design, involving all teachers as respondents. Data were collected using Likert-scale questionnaires and documentation, and analyzed using simple linear regression. The results indicate that principal leadership is categorized as very good, with a mean range of 4.375–4.900, while the effectiveness of the implementation of the Merdeka Curriculum is also categorized as very good, with a mean range of 4.125–4.500. Furthermore, the findings reveal a significant influence of principal leadership on the effectiveness of the implementation of the Merdeka Curriculum, as evidenced by a t-value of 3.875 > t-table value of 2.042 and a significance level of 0.001 < 0.05. The contribution of principal leadership to the effectiveness of curriculum implementation is 45.2%, while the remaining proportion is influenced by other factors such as teacher competence, school culture, school management, and other supporting factors distinct from facilities and infrastructure.